PEMERIKSAAN KOLESTEROL, GULA DARAH DAN ASAM URAT DI DESA GLAGAHARJO KECAMATAN CANGKRINGAN KABUPATEN SLEMAN - Susanto, Nugroho (Jurnal Pengabdian Dharma Bakti, 2021)
SCREENING CHOLESTEROL, GLUCOSE AND URIC ACID IN VILAGE GLAGAHHARJO, SUB-DISTRICT CANGKRINGAN DAN DISTRICT SLEMAN. Glucose, cholesterol and uric acid increasing every years especially elderly. Prevalence in Asia highest Marshall Islands 85% and Indonesia 18%. Elderly increase from 841 million in 2013 to more than 2 billion in 2050. The paper objective to screening risk factors for elderly in Sleman district. Population study is elderly under Cangkringan center health service age 50 - 95. Sample was required 49 elderly. Blood sample 5 ml with aseptic with parameter by Easy Touch GCU. Data were analyzed by SPSS versi 20 with statistic test linear regression with 95% Confidence interval. Mean of age 64,82 years old, body weigh 51,83 kilo, systole blood pressure 155,08 mmHg, diastolic blood pressure 84,98 mmHg, cholesterol 204,67 mg/dl, uric acid 5,463 mg/dl.Key word: blood pressure, cholesterol, elderly